Post-Synthetic Treatment of Layered Nanomaterials for Optimized Performance in Energy Transfer & Storage Devices - Tyndall, Daire (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Controlled syntheses of PbO and NiFe LDH layered nanomaterials were carried out for this work, followed by comprehensive studies to determine the extent to which improvements can be made, in terms of performance in their respective energy applications, by way of post-synthesis processing steps. Namely, particle size control and composite optimization with carbon nanotubes were the principle approaches for enhancing the performance, along with some additional key cell design considerations. NiFe LDH is studied for its electrocatalytic properties. Highly crystalline NiFe hexagonal platelets with high morphological regularity and sub-micrometre lateral dimensions were synthesized using a homogeneous precipitation technique. The hexagons exhibit exceptional electrocatalytic activity for the oxygen evolution reaction (OER), especially in alkaline media, and for this reason have potential applications in water electrolysis for H_2 gas extraction. Considering edge sites are the point of activity, efforts were made in this work to tailor the platelet dimensions within the synthesized dispersions. To this point, synthetic approaches for size control of NiFe LDH platelets have not been transferable based on published work for such processes with other LDH materials and for that reason we instead use post-synthetic treatment techniques to improve edge-site density. Namely, a combination of ultrasonication and centrifugation-driven size-selection steps were applied to the NiFe LDH and the electrocatalytic behaviour towards OER was characterized. Synthesized platelets of mean lateral size = 0.78 ± 0.02 µm can be selectively reduced to values below 0.2 µm with overpotential η = 245 ± 7 mV. Composite optimization allows for further reduction in this value with important long-term stabilizing effects on the system. In recognition of the complex, still-debated mechanism for NiFe LDH alkaline water electrolysis, additional efforts are presented here to determine the factors which govern the short and long term OER performance of the catalyst. It is suggested that a combination of subtle phase changes and gradual leaching of metal components from the LDH structure will govern the catalyst s stability and hence, performance. PbO is another material with significant potential, this time in battery applications as a LIB anode, but requires a degree of processing in order to realise its full potential. Controlled thermal degradation of PbCO3 can be used to synthesize PbO in its phase-pure tetragonal (α) and orthorhombic (β) symmetries. Similar particle size and composite preparation steps can act to reduce long range stress experienced by the material during lithiation, as well as improving the conductivity and ionic diffusion with the crystal. Composites of phase pure tetragonal α-PbO with SWCNTs can outperform commercial polymorphic material, with 670 mAh∙g-1 at 0.1 C and 82% capacity retention through ten cycles. In summary, this thesis aims to explore the utility of simple, transferable steps which can be applied to promising nanomaterials with novelty in energy devices, to greatly enhance their long-term performance and outlook in practical applications.
APPROVED
Keywords: Electrocatalysis, nanotechnology, lithium-ion battery, alkaline water electrolyzer, fuel cell, nanocomposite